Imperial encore : the cultural project of the late British empire - Ritter, Caroline, 1984- (Oakland, California : University of California Press, 2021)
"In the 1930s, British colonial officials introduced broadcasting services, publication bureaus, and film units into Africa under the rubric of colonial development. They used radio, film, and mass-produced books to spread British values and the English language across the continent. This project proved remarkably resilient: well after the end of Britain's imperial rule, many of its cultural institutions remained in place. Through the 1960s and 1970s, African audiences continued to attend Shakespeare performances and to listen to the BBC, while African governments adopted English-language textbooks produced by metropolitan publishing houses. Imperial Encore traces British drama, broadcasting, and publishing in Africa between the 1930s and the 1980s--the half century spanning the end of British colonial rule and the outset of African national rule. Caroline Ritter shows how three major cultural institutions--the British Council, the BBC, and Oxford University Press--integrated their work with British imperial aims, and continued this project well after the end of formal British rule. Tracing these institutions and the media they produced through the tumultuous period of decolonization and its aftermath, Ritter offers the first account of the global footprint of British cultural imperialism"--
Introduction -- Shakespeare in Africa : the British Council and drama export -- "Bringing books to Africans" : publishing in colonial East Africa -- "This is London..." : BBC broadcasting to colonial Africa -- "... Calling Africa" : capturing the Cold War audience -- Patrons of postcolonial culture : British publishers and African writers -- From culture to aid to paid : cultural relations after empire -- Epilogue.
Includes bibliographical references and index.
Caroline Ritter is Assistant Professor of History at Texas State University.
Print version record.
JSTOR
Keywords: Cultural industries -- Africa, English-speaking -- History -- 20th century; Great Britain -- Colonies -- Africa -- Cultural policy; Great Britain -- Relations -- Africa, English-speaking.; Africa, English-speaking -- Relations -- Great Britain; Industries culturelles -- Afrique anglophone -- Histoire -- 20e siècle.; Grande-Bretagne -- Colonies -- Afrique -- Politique culturelle; Afrique anglophone -- Relations -- Grande-Bretagne.; Africa; HISTORY; Media Studies; SOCIAL SCIENCE; International relations; Cultural policy; Cultural industries; British colonies; Great Britain; English-speaking Africa; Africa; 1900-1999; Electronic books; History